Abruptio placenta and its maternal and fetal outcome - Mishra, Ritu; Misra, Aditya Prakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Abruptio placenta is one of the common cause of antepartum haemorrhage and is defined as premature separation of normally implanted placenta. It is more common in second half of pregnancy. Abruptio placenta is serious complication of pregnancy and causes high maternal and neonatal morbidity and mortality. Methods: This retrospective study of abruptio and its maternal and perinatal outcome was carried out between July 2016 and October 2017 at Rama Medical College Hospital and research centre. Results: Incidence of Abruptio placenta is 1.6%. It is most common in the women of age group 30-35 years. 75% of cases were associated with severe pre-eclampsia. Live births were 75% while stillbirths were 25%. PPH occurred in 30% of cases. DIC accounts for 25% of the complication. Conclusions: Abruptio placenta is life threatening complication of pregnancy and it is associated with poor maternal and fetal outcome if not managed appropriately. Hence early diagnosis and prompt resuscitative measures would prevent both perinatal and maternal mortality and morbidity.